Точечный комплекс Кошуля системы полиномов - Сейфуллин, Т.Р. (Видавничий дім "Академперіодика" НАН України, 2008)
A pointed element of the Koszul complex of a system of polynomials is an analog of the pointed distribution depending on parameters.